ANALYSIS OF CAUSES AND EFFECTS OF POOR SANITATION AND HYGIENE IN SECONDARY SCHOOLS IN ABA METROPOLIS, ABIA STATE, NIGERIA (UNIZIK Journal of Educational Management and Policy, 2024)
This study analyzed the causes and effects of poor sanitation and hygiene in secondary schools in Abametropolis, Abia State, Nigeria. Descriptive research survey design was adopted for the study. Thereare 7 Local government areas in Aba metropolis in which 120 respondents were randomly selectedthrough purposive random sampling technique guided by research advisor 2006. Three researchquestions guided the study. Mean scores were used as statistical tools for the study. Findings showedthat the respondents agreed to the main causes, and the effects of poor sanitation in secondary schoolswith a grand mean of scores of 2.88, 3.08 and which is greater than the critical mean score of 2.50. Itwas recommended that the government and non-governmental organizations should make adequateprovision of toilets and urinary facilities for the schools.
Keywords: Causes, Effects, School Hygiene, School Sanitation